Comparative study of oral and salivary parameters in patients with and without loss of bone mass - Igor Figueiredo PEREIRA; Cláudia Borges BRASILEIRO; Núbia Priscilla KLEPERON; Mauro Henrique Nogueira Guimarães de ABREU; Tarcília Aparecida da SILVA; Ricardo Alves MESQUITA; Tania Mara Pimenta AMARAL (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract Osteoporosis is an insidious and increasingly prevalent disease that can cause fractures and affect patients' quality of life. The current study comparatively evaluates patients with and without loss of bone mass in terms of salivary calcium, viscosity, and pH. A controlled cross-sectional study was conducted in two groups of 32 postmenopausal women subjected to a bone densitometry scan and later referred for dental management at the Federal University of Minas Gerais, Brazil. The patients were assigned to two groups: Group 1 - patients with low bone mineral density (BMD) and Group 2 - patients without bone mineral changes. The following salivary parameters were evaluated: calcium concentration, flow rate, viscosity, pH, and average total protein. An oral examination was performed for assessment of DMFT variables and tongue coating. Data were analyzed using descriptive and inferential statistics, adopting a p-value < 0.05. The patients' mean age was 60 years (± 7.35). Salivary flow, pH, and viscosity were similar among the groups. Average total protein was 14.8 mg/mL and 19.0 mg/mL in Groups 1 and 2, respectively. Tongue coating and salivary calcium levels were significantly higher in Group 1 (p < 0.001). Salivary calcium is an important screening tool and may eventually be used for the diagnosis of bone mineral changes.